Pembelajaran PAKBP dengan Metode PBL Berbantuan E-LKPD sebagai Upaya Peningkatan Bernalar Kritis Fase C Kelas 6 SD Katolik Santa Maria 1 Malang - Whanarian Mukti Cahyo; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The learning method applied in the 6th grade at SD Katolik Santa Maria 1 Malang is still lacking in variety, resulting in a low level of critical thinking among students and the failure to meet the target outcomes in the proficient and skilled categories. This study aims to improve the critical thinking character dimension and achieve target outcomes through the implementation of the Problem Based Learning (PBL) method supported by E-LKPD. This classroom action research was conducted in two cycles with the material